Potential HIV transmission risk among spouses: marriage intention and expected extramarital male-to-male sex among single men who have sex with men in Hunan, China. (6th June 2019) - Wu, Weizi; Yan, Xiaochen; Zhang, Xiaoxia; Goldsamt, Lloyd; Chi, Yuanyuan; Huang, Daoping; Li, Xianhong
Abstract : Objective: The HIV epidemic in China is shifting from the high-risk groups of men who have sex with men (MSM), injection drug users and sex workers to the general population, and sexual contact among spouses is assumed to be one route of transmission. Our objective was to determine the intention to marry and the expected extramarital male-to-male sex among single Chinese MSM, in order to estimate the potential HIV transmission risk among MSM living with HIV and their female spouses. Methods: We conducted a web-based, cross-sectional survey between May 2016 and May 2017. A questionnaire covering sociodemographic characteristics, sexual behaviours, HIV-related and homosexuality-related stigma, marriage intention, and expected extramarital sexual behaviours was completed by 556 single MSM in Hunan, China. Descriptive statistics, χ 2 test, two-sample t-test and multivariate logistic regression analysis were performed. Results: Currently 48.9% of the participants intended to marry a woman in their lifetime, and 91% of them reported that they would continue to have sex with men after getting married. Those who were living with parents (OR=2.26), self-identified as bisexual (OR=2.57), had at least one heterosexual partner in the previous 6 months (OR=0.33) and perceived a higher level of self-homosexual stigma (OR=1.78) had greater intention to marry a woman. Conclusion: Nearly half of Chinese MSM intend to marry women, which has significantly dropped from the estimated percentage more than 10 years ago for Chinese MSM. However, the expectation of extramarital homosexual behaviours was common in these men. Sexual and gender minority stresses especially from family members, homosexual identity assertiveness and related stigma were the main factors for marriage intention, which should be addressed in future studies and practices.